Microstructure Evolution of Mg96.9Gd2.7Zn0.4 Alloy Containing Multiple Phases Prepared by Spark Plasma Sintering Method - Zhiyong Xue; Xiuzhu Han; Wenbo Luo; Zhiyong Zhou; Zhizhong Cheng; Wenhan Li; Yanlin Wang (Metals, 2020)
The synergic strengthening of multiple phases is an essential way to achieve high-performance Mg alloys. Herein, Mg-Gd-Zn alloy containing four phases was prepared by rapid solidification (RS) ribbons and spark plasma sintering (SPS). The microstructure of the alloy consisted of α-Mg, nanosized β1 phase particles, lamellar long period stacking ordered (LPSO) phase, and β′ phase precipitates. The microstructural evolution was also investigated. The results show that the metastable β1 phase was formed in the as-cast solidification through rapid solidification, because both Zn atoms and the short holding-time at molten liquid facilitated the formation of the β1 phase. The β1 phase grew from 35.6 to 154 nm during the sintering process. Meanwhile, the fine lamellar LPSO phase was simultaneously formed after the Zn-Gd clusters were generated from the supersaturated solid solution, and the width of the LPSO phase was only in the range of 2–30 nm. The third strengthening phase, the metastable β′ phase, was obtained by aging treatment. The results of hardness testing implied that the hardness of the alloy containing the aforementioned three nanosized strengthening phases significantly improved about 47% to 126 HV compared with that of the as-cast ingot.